District nurses' experiences of caring for leg ulcers in accordance with clinical guidelines: a grounded theory study. Issue 1 (1st January 2017) - Lagerin, Annica; Hylander, Ingrid; Törnkvist, Lena
ABSTRACT: This qualitative study used the grounded theory method to investigate district nurses' experiences of caring for leg ulcers in accordance with clinical guidelines at seven primary health care centres in Stockholm, Sweden. Group interviews were conducted with 30 nurses. The results describe how district nurses strive to stay on track in order to follow clinical guidelines and remain motivated despite prolonged wound treatment and feelings of hopelessness. Three main obstacles to following the guidelines were found. District nurses used compensating strategies so the obstacles would not lead to negative consequences. If the compensating strategies were insufficient, perceived prolonged wound treatment and feelings of hopelessness could result. District nurses then used motivating strategies to overcome these feelings of hopelessness. Sometimes, despite the motivating strategies, treatment in accordance with guidelines could not be achieved. With some patients, district nurses had to compromise and follow the guidelines as far as possible.